دراسة التباينات الوراثية لمجموعة من الطرز الوراثية من النعناع المائي Mentha aquatica المنتشرة في المنطقة الساحلية باستخدام تقنية الـ PCR – RAPD - يوسف, عزيزة; ديب, جورج; بيطار, غادة (Latakia University Journal -Biological Sciences Series, 2019)
جمعت عينات من نبات النعناع المائي Mentha aquatica (Water Mint) من سبع مناطق توزعت في الساحل السوري ( اللاذقية وطرطوس ). تمت دراسة التباينات باستخدام تقانة الـ RAPD بهدف تحديد الهوية الوراثية للطرز المدروسة من خلال استخدام ثمانية عشرة بادئة ، ولكن فقط (7) بادئات أظهرت مكاثرة للـDNA، وتم حساب معامل التشابه والبعد الوراثي باعتماد طريقة (Nei and Li ; 1979).وأنشئت شجرة القرابة الوراثية (التدرج العنقودي ) أظهرت هذه الدراسة النتائج التالية: - تراوحت قيمة معامل التشابه بين الطرز المختلفة بين (0.53 -0.02) وهناك تدرج في التباينات الوراثية للطرز المدروسة ما بين هذه القيم المحسوبة لمعامل التشابه والبعد الوراثي. - أظهرت شجرة القرابة الوراثية تبايناً في توزع الطرز الوراثية ، في المناطق المختلفة المدروسة ، تبعاً للبعد الوراثي فيما بينها . - سمحت نتائج هذه الدراسة بتحديد بادئات يمكن استخدامها بوصفها مؤشرات جزيئية في برامج تحسين نبات النعناع بوصفه نباتاً طبياً وغذائياً, كما أظهر استخدام هذه التقنية كفاءة في دراسة علاقات القرابة لنبات النعناع في مواقع الدراسة المختلفة . Samples of water mentha (Mentha aquatic) were collected from seven sites distributed along Syrian coast (Lattakia & Tartous). The samples were studied morphological and genetically using RAPD-PCR technique in order to identify the genetic identity of the studied types using 18 primers. However, only seven primers showed DNA amplification. The similarity coefficient as well as genetic distance were calculated using the method cited by (Neiandli ,1979). Dendogram was constructed. This study showed that the range of similarity coefficient between different types was ( 0.02 – 0.53 ). Consequently, there was gradation in genetic variants of studied types between the calculated values for similarity coefficient and genetic relationship. The Dendogram showed variance presence in distribution of the genetic types in the regions studied depending the genetic distance. The results of this study also showed the possibility of detection of primers using RAPD that can be used as precise indicators in programs of Mentha improvements as medical and nutritional plant. In addition, the study showed the efficacy of this technique in studying the relationships of mentha in different areas of study sites.